Maternal Prenatal External Locus of Control and Reduced Mathematical and Science Abilities in Their Offspring: A Longitudinal Birth Cohort Study - Golding, Jean; Gregory, Steven; Ellis, Genette; Nunes, Terezinha; Bryant, Peter; Iles-Caven, Yasmin; Nowicki, Stephen (Frontiers in Psychology, 2019)
A personality scale that identifies individuals’ general attitude to what happens to them as largely a matter of luck or fate or of powerful others (externality) or whether they feel they can influence the consequences (internality) is known as locus of control (LOC). A continuous scale can distinguish those who are more external from those who are more internal. Lower scholastic achievement is associated with externality and higher achievement with internality, but little is known about the association of parental LOC on children’s academic performance. Data collected within the Avon Longitudinal Study of Parents and Children (ALSPAC) are analysed to assess associations between the mothers’ LOC orientation, measured during pregnancy, and their children’s abilities in mathematics and science reasoning. We found that maternal external LOC is associated with lower scores for her child assessed by tests measuring mental arithmetic as well as understanding of mathematical and scientific concepts. Additionally, we determined the extent to which three separate sets of factors previously found to positively influence the developing child’s ability mediate these findings: (a) perinatal and infant exposures, such as prenatal smoking, binge drinking, consumption of oily fish, and postnatal breast feeding; (b) parenting attitudes and strategies; and (c) the interface of the parents with their child’s school. The three factors identify at least 50% of the mechanism by which maternal externality is associated with poor academic outcomes in her child and may be candidates for further investigation as possible intervention targets.